Alcohol consumption and the risk for prostate cancer in the European Prospective Investigation into Cancer and Nutrition. - Rohrmann, S; Linseisen, J; Key, T; Jensen, M; Overvad, K; Johnsen, N; Tjønneland, A; Kaaks, R; Bergmann, M; Weikert, C; Naska, A; Trichopoulou, A; et al. (2008)
Alcohol is a risk factor for several types of cancer. However, the results for prostate cancer have been inconsistent, with most studies showing no association. Within the European Prospective Investigation into Cancer and Nutrition, detailed information were collected from 142,607 male participants on the intake of alcoholic beverages at recruitment (for 100% of the cohort) and over lifetime (for 76% of the cohort) between 1992 and 2000. During a median follow-up of 8.7 years, 2,655 prostate cancer cases were observed. Multivariate Cox proportional hazard models were used to examine the association of alcohol consumption at recruitment and average lifetime alcohol consumption with prostate cancer adjusted for age, center, smoking, height, weight, physical activity, and nonalcohol energy intake. Overall, neither alcohol consumption at baseline nor average lifetime alcohol consumption was associated with the risk for prostate cancer in this cohort of men. Men who consumed >or=60 g alcohol per day had a relative risk of 0.88 [95% confidence interval (95% CI) 0.72-1.08] compared with men with an intake of 0.1-4.9 g/d; the respective relative risk for average lifetime intake was 1.09 (95% CI, 0.86-1.39). For advanced prostate cancer (n = 537), the relative risks for >or=60 and 0.1-4.9 g alcohol per day at baseline were 0.98 (95% CI, 0.66-1.44) and 1.28 (95% CI, 0.79-2-07), respectively, for average lifetime intake. No statistically significant association was observed for alcohol intake from specific alcoholic beverages. Our results indicate no association between the consumption of alcohol and prostate cancer in this cohort of European men.